Strategi Kreatif Digital Content Akun Instagram @Ilovelampung Sebagai Media Informatif Provinsi Lampung - Hagi Julio Salas; Della Monica; Arif Budianto; Muhammad Al Ghiyats Yudho Pratama; Ramdhan Azwar Renata (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
New media, particularly social media platforms like Instagram, have become strategic marketing communication tools. Instagram offers a variety of engaging features that allow users to share information in the form of text, photos, and videos. This study examines the communication strategy used in the content of the Instagram account @ilovelampung, which provides information about Lampung Province. By employing the SOSTAC model (Situation Analysis, Objectives, Strategy, Tactics, Action, and Control), this research aims to identify and understand the content communication strategy implemented by @ilovelampung. The agenda-setting theory is applied to analyze how the objectives and role of @ilovelampung's content contribute to shaping public opinion about Lampung Province. This study adopts a qualitative descriptive method. The findings reveal that the digital content strategy of @ilovelampung, utilizing the SOSTAC marketing communication model, has effectively enhanced awareness and attractiveness toward Lampung Province. The account employs 11 strategies and 9 tactics to achieve its objectives. @ilovelampung strategically establishes specific agendas in each piece of content, primarily aimed at countering negative perceptions about Lampung Province. It does so by highlighting positive elements such as natural beauty, cultural heritage, culinary attractions, and local SMEs, thereby shaping a more favorable image of Lampung among the broader public.